Modeling of soil–rock mixture landslides with the generalized interpolation material point method - Li, Xia; Xie, Peng-Fei; Zheng, Yong; Liu, Jie; Wang, Lie-Jian; He, Kai-Yuan; Jiang, Tao (Frontiers in Earth Science, 2022)
The new numerical model for studying the dynamic evolution of soil-rock mixture (SRM) landslides is presented in this paper. The numerical model based on the generalized interpolation material point method (GIMP) analyzes a simplified slope. The gravity is linearly loaded, and the linear elastic model is used to update the stress to obtain the initial state of the slope. A small soil cohesion is set to trigger the slope sliding until the equilibrium state is reached again. During this period, the elastic-plastic material model based on the Drucker-Prager criterion is adopted for soil and stones. The differences in dynamic evolution between homogeneous soil slope and soil-rock mixture slope are studied. Under the same stone content, the influence of the size and shape of stone on the dynamic evolution of slope is studied.